Characterization of the complete mitogenome data of Ischyja marapok (Lepidoptera: Noctuoidea: Erebidae) from Malaysia - Marylin Miga; Puteri Nur Syahzanani Jahari; Sivachandran Parimannan; Heera Rajandas; Muhammad Abu Bakar Abdul-Latiff; Yap Jing Wei; Mohd Shahir Shamsir; Faezah Mohd Salleh (Data in Brief, 2023)
Ischyja marapok is a moth species from the genus Ischyja, a member of the Lepidoptera family, Erebidae. Due to their wide variation, this family constitutes the largest described species, however, the mitogenome dataset on the genus Ischyja is scarce. Hence, the mitochondrial genome dataset of Ischyja marapok from Malaysia was completely sequenced using the next-generation sequencing technology, Illumina NovaSeq 6000 and analyzed. The mitogenome has a sequence length of 15,421 bp, consisting of 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs) and a control region. The mitogenome is A + T biased (80.6%), with the base composition of A (39.2%), T (41.4%), C (11.9%) and G (7.5%). Among the 13 PCGs, 12 were initiated by the standard ATN codon, except for COX1 which utilizes the CGA start codon. Two PCGs were terminated with an incomplete stop codon T, while others ended with a TAA codon. Phylogenetic tree analyses showed that the sequenced I. marapok resides within the Erebinae subfamily and is closely related to Ischyja manlia (MW664367) with high bootstrap support and posterior probabilities. This dataset presented the mitogenome data of I. marapok from Malaysia, which is valuable for further research of their phylogeny and the diversification of the Ischyja genus. Also, this dataset can be implemented and used as references to assess environmental changes in the terrestrial ecosystem via environmental DNA approaches. The mitogenome of I. marapok is available in GenBank under the accession number ON165249.